Add-on Pricing, Consumer Myopia and Regulatory Intervention - Ulrich Schüwer; Michael Kosfeld (Verein für Socialpolitik, 2010)
Previous research shows that firms may offer excessively high (and shrouded) add-on prices in competitive markets when some consumers are myopic. We analyze the effects of regulatory intervention via educating myopic consumers on equilibrium strategies of firms, consumer protection and welfare. Our model allows firms to price discriminate between consumers. We show that intervention may actually decrease social welfare and weaken consumer protection if regulatory efforts are insufficient to alter the equilibrium strategy of firms. In consequence, regulation may do more harm than good and hence should only be considered if the regulator can be sure to have a good understanding of pricing strategies in an industry.
Keywords: L50; D40; D80; 330; bounded rationality; information suppression; regulation; social welfare; consumer protection